Perbedaan Persepsi dan Kemandirian Belajar Siswa SMA Terhadap Pembelajaran Daring Ditinjau Dari Gender - Fery Fauzan; Maman Fathurrohman; Syamsuri Syamsuri (Universitas Sultan Ageng Tirtayasa, 2020)
In learning mathematics, students' affective abilities are also important to pay attention to in achieving learning goals. The affective ability referred to is the perception and independence of student learning. This study aims to obtain information: (1) knowing there are differences in perceptions between students in class XI and XII IPA on online learning (2) knowing that there are differences in perceptions between male students and female students regarding online learning (3) knowing there are differences in learning independence Between class XI and XII IPA students on online learning (4) there are differences in learning independence between male students and female students towards online learning. This research is a descriptive quantitative research. The research subjects were 231 respondents. Data collection using a questionnaire instrument to collect data on students' perceptions and learning independence. Based on the calculation results, the average percentage of students' perceptions of online learning was 38.44%. This means that almost half of students have a perception of learning mathematics using an online model. While the average percentage of students' learning independence was 46.96%. This means that almost half of the students are independent in learning mathematics. The results of the calculation of the Mann Whitney test show that (1) the significant value is 0.0055, so there is a difference in perceptions between class XI and XII IPA students on online learning (2) the Sig value is 0.095, so there is no difference in the perception of male students and female students towards online learning. (3) the Sig value is 0.095, so it can be concluded that there is no difference in independence between class XI and XII IPA students on online learning (4) the Sig value is 0.162, so there is no difference in independence between male students and female students on online learning